Ondansetron, alfentanil and nitrous oxide in the prevention of pain on injection of propofol - Drašković Biljana; Knežević Sofija; Radovanović Dragana; Rakić Goran (Srpski Arhiv za Celokupno Lekarstvo, 2013)
Introduction. Propofol is a widely used intravenous anesthetic with a number of advantages over intravenous anesthetics used so far. The leading side effect is pain on injection. Objective. Aim of the study was to determine the impact of ondansetron, nitrous oxide and alfentanil on reducing pain during propofol application. Methods. The paper presents a prospective, randomized, single blind study. The study included 120 patients of ASA class I and II, who underwent elective surgery under general anesthesia using propofol for the induction of anesthesia. The patients were divided into four equal groups of 30 patients. The control group received a few milliliters of saline, N group the mixture of nitric oxide and oxygen, O group ondansetron and group A received alfentanil. In all patients, venous occlusion was performed for 60 seconds. Pain assessment was based on the criteria and the score by McCrirrick and Hunter. Results. Pain after the application of propofol was present in 47 (39.2%) patients. The highest frequency of pain was recorded in the control group (18, 60%), and significantly lower (p=0.009) in the patients who received ondansetron (8; 26.7%) and (p=0.020), alfentanil (9; 30%). The statistical analysis proved that there was a significant relationship between the groups and the scale of pain (χ2=13.849, p=0.031). Conclusion. Based on the results of our study we can conclude that intravenous ondansetron and alfentanil with venous occlusion can effectively prevent pain during IV use of propofol.